(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the pain-relieving and mobility-improving effects of thread-embedding acupuncture combined with acupressure, electroacupuncture, and aquapuncture in patients with knee osteoarthritis. Methods: A controlled, prospective clinical trial with pre- and post-treatment comparisons was conducted from May 2024 to June 2025 on 60 patients diagnosed with knee osteoarthritis and treated at the Department of Traditional Medicine, Military Hospital 103. Results: After 15 days of treatment, there was a significant improvement in VAS scores, Lequesne index, knee flexion range of motion, and heel-to-buttock distance compared to baseline (p < 0.05) in both groups. The degree of improvement in these indices was greater in the study group and showed statistically significant differences compared to the control group (p < 0.05). Conclusion: The combination of thread-embedding acupuncture, acupressure, electroacupuncture, and aquapuncture was effective in reducing pain and improving joint mobility and Lequesne index scores in patients with knee osteoarthritis.